Description of a new weakfish, Cynoscion nortoni, from Ecuador with a note on the distribution of Umbrina bussingi (Perciformes: Sciaenidae) - Béarez, Philippe (2001)
A new sciaenid was found at a fish market on the Ecuadorian coast. Cynoscion nortoni, described from 11 specimens, is characterised by a relatively large eye, a long head and pectoral fin, a high dorsal fin-ray count and a dark, steel grey colour on its dorsum. The specimens were captured over the continental shelf with a long line at depths between 100 and 200 meters. Another deep water species, Umbrina bussingi, is recorded for the first time from southern Colombia.